2018
DOI: 10.3390/molecules23123349
|View full text |Cite
|
Sign up to set email alerts
|

Permeability Characteristics of a New Antifungal Topical Amphotericin B Formulation with γ-Cyclodextrins

Abstract: Amphotericin B is a low soluble broad-spectrum antifungal agent. Cyclodextrins can be added to amphotericin formulations to enhance both their solubility and antifungal properties. Semisolid amphotericin formulations containing gamma cyclodextrin (AGCD) were prepared and compared with two reference formulations—one of them without any solubility enhancer (A) and the other with DMSO (ADMSO). Rheological, the permeability through hairless mouse skin and antifungal characteristics of the different formulations we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…or oral routes, in terms of patient compliance and AmB therapeutic performance [182,183] despite the distinct physicochemical nature of AmB that compromises its skin permeation. Permeability enhancers such as dimethyl sulfoxide (DMSO) and cyclodextrins (CDs) have been added to AmB formulations to improve drug solubility [224]. Semisolid AmB topical formulations with added γ-CD showed shear-thinning and thixotropic behavior, improved skin permeability, and enhanced in vitro antifungal efficacy against Candida species and Sacharomyces cerevisiae compared with an AmB reference formulation containing no solubility enhancers [224].…”
Section: Nanoemulsionsmentioning
confidence: 99%
See 1 more Smart Citation
“…or oral routes, in terms of patient compliance and AmB therapeutic performance [182,183] despite the distinct physicochemical nature of AmB that compromises its skin permeation. Permeability enhancers such as dimethyl sulfoxide (DMSO) and cyclodextrins (CDs) have been added to AmB formulations to improve drug solubility [224]. Semisolid AmB topical formulations with added γ-CD showed shear-thinning and thixotropic behavior, improved skin permeability, and enhanced in vitro antifungal efficacy against Candida species and Sacharomyces cerevisiae compared with an AmB reference formulation containing no solubility enhancers [224].…”
Section: Nanoemulsionsmentioning
confidence: 99%
“…Permeability enhancers such as dimethyl sulfoxide (DMSO) and cyclodextrins (CDs) have been added to AmB formulations to improve drug solubility [224]. Semisolid AmB topical formulations with added γ-CD showed shear-thinning and thixotropic behavior, improved skin permeability, and enhanced in vitro antifungal efficacy against Candida species and Sacharomyces cerevisiae compared with an AmB reference formulation containing no solubility enhancers [224]. Several studies on NE development for topical AmB delivery have shown their suitability for the treatment of skin fungal infections [180][181][182][183][184], based on the synergistic effects resulting from the combination of lipids and surfactants with the antifungal drug [181].…”
Section: Nanoemulsionsmentioning
confidence: 99%
“…Ex vivo permeation studies were also performed in static Franz diffusion cells (as described in Section 2.5.2) using the male rat epidermis as a skin model; this was clamped between the donor and receptor compartments with the stratum corneum side facing up [20]. The rat skin was treated as described previously with permission obtained from the Ethics Commitment Jury [21]. The fur and lipids were removed from the skin.…”
Section: Encapsulation Efficiency and Drugmentioning
confidence: 99%
“…A topically administered AmB formulation can bypass these disadvantages from invasive administration techniques and thus permit treatment of localized infections in skin or mucous membranes [17]. However, the higher molecular weight (926 Da) and low solubility in water of AmB could limit its passage through the skin [18]. These complications could be circumvented by incorporating excipients with permeationenhancing properties that promote the penetration of drugs through the stratum corneum (SC) and its distribution to the epidermis and dermis [19].…”
Section: Introductionmentioning
confidence: 99%